Web-based training: a new paradigm in computer-assisted instruction in medicine - Haag, Martin; Maylein, Leonhard; Leven, Franz-Josef; Tönshoff, Burkhard; Haux, Reinhold (International journal of medical informatics, 1999)
Computer-assisted instruction (CAI) programs based on internet technologies, especially on the world wide web (WWW), provide new opportunities in medical education. The aim of this paper is to examine different aspects of such programs, which we call ‘web-based training (WBT) programs’, and to differentiate them from conventional CAI programs. First, we will distinguish five different interaction types: presentation; browsing; tutorial dialogue; drill and practice; and simulation. In contrast to conventional CAI, there are four architectural types of WBT programs: client-based; remote data and knowledge; distributed teaching; and server-based. We will discuss the implications of the different architectures for developing WBT software. WBT programs have to meet other requirements than conventional CAI programs. The most important tools and programming languages for developing WBT programs will be listed and assigned to the architecture types. For the future, we expect a trend from conventional CAI towards WBT programs.
Gesehen am 03.07.2019